Menguji Niat Berwirausaha pada Mahasiswa di Jakarta - Siti Salsabila; Melianti Saruksuk; Siti Nikmaturofiqoh; Usep Suhud; Amalia Putri Maharani (Fakultas Ekonomi Universitas Negeri Jakarta, 2021)
This study aims to examine the factors that influence the intention to become an entrepreneur among students at Jakarta. There are five variables used to measure, namely entrepreneurial education, entrepreneurial parents, outcome expectation, leadership skills, risk taking. Data collection was carried out in Jakarta period in April - May 2021. Data was collected using an online questionnaire and respondents were selected using a random sampling techniques. The total respondents in this study were 211 consisting of 108 men and 103 women who were doing the study with an age range of 17 - 30 years. The data will be processed using Exploratory Factor Analysis (EFA) and Structural Equation Models (SEM). The result is that leadership skills have a positive and significant effect on intention to become an entrepreneur, risk taking has a positive and significant effect on intention to become an entrepreneur. Outcome expectation, entrepreneurial education and entrepreneurial parents do not have a positive and significant effect on intention to become an entrepreneur.